Genome-wide and transcriptome analysis of PdWRKY transcription factors in date palm (Phoenix dactylifera) revealing insights into heat and drought stress tolerance - Ibrahim Khan; Lubna; Saqib Bilal; Ashraf M. M. Abdelbacki; Sang-Mo Kang; Ahmed AL-Harrasi; Sajjad Asaf; In-Jung Lee (BMC Genomics)
Abstract Genomic and transcriptomic studies on date palm (Phoenix dactylifera) are still inadequate, but several studies have contributed to understanding its genetic makeup, especially in the Khalas cultivar. Looking at the extensive importance of WRKY transcription factors (TFs) in plant growth, development and defense responses to various biotic and abiotic stresses, we conducted a study to identify and functionally annotate the WRKY TFs of P. dactylifera, with a particular focus on their involvement in drought and heat stress. A total of 73 PdWRKY TFs were curated and classified into 7 and 17 clades through comparative phylogenetic analysis and orthologous comparison of the WRKY TFs from the extensively studied genomes of Arabidopsis thaliana and Oryza sativa, respectively. Our findings show that 52% of PdWRKYs have strong homology with OsWRKYs, while only 9 PdWRKYs have orthologous relationships with AtWRKYs. This indicates a divergence in evolutionary patterns, likely due to gene duplications and losses in rice, Arabidopsis, and date palm, that occurred both before and after the last common ancestor of these species. Our comprehensive analysis of gene structures, conserved motifs, and protein-protein interactions confirmed functional similarities among many PdWRKYs. The GO and KEGG pathway enrichment analyses validate that PdWRKY genes have significant functional roles in various molecular, cellular, and biological processes. The transcriptomics analysis revealed that heat stress resulted in upregulating 7 genes (12.2%) and downregulating 10 PdWRKY genes (17.5%). With combined drought and heat stress, 15 genes (26.3%) were upregulated, and 9 genes (15.78%) were downregulated. Notably PdWRKYs genes such as LOC103723396 (WRKY35) and LOC103718774 (WRKY1) showed significantly higher while LOC103713231(WRKY28), LOC103721327(WRKY72, LOC103721580 (WRKY50), LOC120110335 (WRKY70), and LOC103707788 (WRKY71) showed significantly lower expression under drought and heat stress conditions compared to control plants, indicating their vital role in adaptation and tolerance mechanisms against these environmental stresses. The current study will highlight the essential role of comprehensive genomic and transcriptomic studies for developing innovative approaches to promote plant growth in adverse conditions. Further studies on these PdWRKY genes could provide insights into their specific roles and mechanisms in stress response pathways in date palms, potentially leading to strategies for improving stress resilience in this important crop species.